Nasal overshoot: Probably a new entity - V Raveenthiran (EL-Med-Pub, 2021)
Background: Congenital masses of the nasal tip are extremely rare. Differential diagnoses include nasal-tip teratoma, nasal chondromesenchymal hamartoma (NCMH), and heterotopic nasal glioma. Herein, the case of a newborn is reported that does not match with any of these differential diagnoses.  Case presentation: A newborn male presented with a congenital pedunculated mass arising from the nasal columella. The mass was symmetrically bilobed which is very unusual for any hamartomatous or neoplastic lesions. Histologically, it was composed of cartilage and ciliated epithelium. Conclusion: Based on the uniqueness of the case it is hypothesized that the lesion could be an embryological error of frontonasal process overshoot defying, hitherto unknown, controlling mechanism. More research is needed to know how the morphometric proportion of the human body is determined by Nature.